Evaluating the Impact of Yoga-Based Interventions on High Blood Pressure: systemic review - Praveena, S.; Rajalakshmi, S.; Premila, E.; Banupriya, C. (Journal of Neonatal Surgery, 2025)
Background: Hypertension is a major global health concern requiring effective management. While medications are common, complementary therapies like yoga have gained interest for their potential benefits. This systematic review evaluates the efficacy of yoga therapy in lowering blood pressure among hypertensive individuals. Methods: A systematic search of PubMed, CINAHL, and Cochrane Library was performed for studies published between January 2000 and October 2023. Randomized controlled trials and clinical intervention studies assessing yoga’s effects on hypertensive patients were included. Two reviewers independently extracted data on study design, participant characteristics, interventions, and blood pressure outcomes. Meta-analysis was conducted where data were comparable. Results: Eight eligible studies involving 1,005 participants with varied hypertension severity were analyzed. Yoga styles included Hatha, Iyengar, and Vinyasa, with intervention durations of 8 to 12 weeks. Pooled results showed significant reductions in systolic blood pressure (mean difference = -10.62 mmHg; 95% CI: -13.14 to -8.10; p < 0.001) and diastolic blood pressure (mean difference = -6.98 mmHg; 95% CI: -8.86 to -5.10; p < 0.001) post-intervention. Effect sizes ranged from moderate to large (Cohen’s d 0.5–1.4), indicating clinically meaningful improvements. Conclusion: This review provides strong evidence supporting yoga therapy as an effective and safe adjunct to conventional hypertension treatment. Future studies should examine long-term effects and explore yoga's integration into routine hypertension care.